Kepelbagaian pendekatan pengajaran dan pembelajaran rasulullah (s.a.w) demi menjana pendidikan yang berkesan - Hashim, Che Noraini (Yayasan Takmir, 2008)
Globalization has brought about many drastic changes in our life including in education. The explosion of infromation and communication technologies, advancement in educational reseraches and practices have compelled teachers to be more sensitive to change. They need to consistenly improve their teaching quality. The traditional lecture method of 'talk and chalk' and the 'trial and error' method are inadequate to produce excellent students today. Although many teachers have been exposed to different theories and methods of teaching and learning, the outcomes have not been promising. This paper discusses the approaches, strategies and methods such as halaqah, lecture, demonstration and story telling, that have been used by the Prophet Muhammad (pbuh) to obtain a generation of unique, God-conscious individuals and some proposition on how to obtain optimum results in learning.